Implementing the Draft W3C Semantic Sensor Network Ontology - O'SULLIVAN, DECLAN; BRENNAN, ROB (multicon verlag and IEEE Xplore, 2010)
This paper examines the feasibility of using ontologies to model generic sensor networks, based on the capabilities of the current generation of ontology tools. The creation of such an ontology, the current tool’s capacity to adequately maintain it, and its potential functionality, as part of a larger semantic system are addressed here. These topics were addressed by constructing a generic sensor ontology and attempting to implement it as part of a larger semantic system. The process and the conclusions drawn from it are described below.
7th IEEE International Workshop on Managing Ubiquitous Communications and Services (MUCS)
PUBLISHED
PerCom 2010, Mannheim, Germany
Keywords: Sensor Networks; Intelligent Content & Communications; Telecommunications